Invited Review: Emerging functions of histone H3 mutations in paediatric diffuse high‐grade gliomas. (7th January 2020) - Kasper, L. H.; Baker, S. J.
Abstract : Paediatric diffuse high‐grade gliomas (pHGG) are rare, but deadly tumours. The discovery of recurrent mutations in the tail of histone H3, changing lysine 27 to methionine, or glycine 34 to arginine or valine, has illuminated a critical role for epigenetic dysregulation in the aetiology of childhood gliomas and opened new avenues of exploration that have resulted in numerous advances for the field. In this review, we describe the current models of H3K27M mutant cancer that are available to the research community and the insights they have provided on tumour biology and the epigenetic and transcriptional effects of histone mutations. We also review the current understanding of the H3G34R/V mutation and the therapeutic outlook for the treatment of pHGG.